PENGARUH UKURAN PERUSAHAAN, OPINI AUIDT, PROFITABILITAS, KOMPLEKSITAS OPERASI, DAN LEVERAGE TERHADAP AUDIT DELAY - Shintia Ananda (2021)
This research was conducted that aims to determine the effect of company size, audit opinion, profitability, operational complexity, and leverage on audit delay. The sample in this study consisted of 65 companies in the trade, service, and investment sector listed on the Indonesia Stock Exchange in the 2016-2020 period, which were selected using purposive sampling technique. Testing the hypothesis in this study was used Multiple Linier Regression analysis with the SPSS version 25. Simultaneously the result show that company size, audit opinion, profitability, operational complexity, and leverage have a significant effect on audit delay. Then partially the results show that audit opinion and profitability has a negative and significant effect on audit delay, and operational complexity has a positive and significant effect on audit delay. While company size and leverage do not have a significant effect on audit delay.